A multifunctional high-speed spindle for micromachining medical materials. (17th September 2009) - Jackson, Mark J.; Xu, Chengying; Ahmed, Waqar
The efficiency of micro cutting tools that are used in high-speed air turbine spindles depends on the rotational speed of the rotor, especially when machining medical materials such as titanium alloys. A high-pressure variation on the surface of the rotor causes the rotor to retard and this severely limits the reliability and durability of high-speed spindles to support new developments in the developing area of micromachining. A variety of spindle designs are proposed and numerical simulations carried out for each design using FLUENT software. The results revealed that changes in the rotor, inlet and outlet geometries affect the pressure distribution on the rotor significantly. The optimum design was identified based on the lowest pressure variation on the rotor surface obtained from the FLUENT results. Spinning the rotor at very high speeds provides a new direction in the development of mechanical micromachining.